2019
DOI: 10.1155/2019/7219297
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mesenchymal Stromal Cell Immunomodulation for Treating Conditions Influenced by the Immune System

Abstract: Mesenchymal stromal cells (MSCs), formerly known as mesenchymal stem cells, are nonhematopoietic multipotent cells and are emerging worldwide as the most clinically used and promising source for allogeneic cell therapy. MSCs, initially obtained from bone marrow, can be derived from several other tissues, such as adipose tissue, placenta, and umbilical cord. Diversity in tissue sourcing and manufacturing procedures has significant effects on MSC products. However, in 2006, a minimal set of standard criteria has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 121 publications
(129 reference statements)
1
24
0
Order By: Relevance
“…Regarding innate immunity, they notably decrease the production of reactive oxygen species by neutrophils and promote the M2 anti-inflammatory phenotype of macrophages. 9 MSCs influence the phenotype of immune cells and their cytokine secretions. However, this immunomodulation seems to depend on the inflammatory context.…”
Section: Mesenchymal Stem/ Stromal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding innate immunity, they notably decrease the production of reactive oxygen species by neutrophils and promote the M2 anti-inflammatory phenotype of macrophages. 9 MSCs influence the phenotype of immune cells and their cytokine secretions. However, this immunomodulation seems to depend on the inflammatory context.…”
Section: Mesenchymal Stem/ Stromal Cellsmentioning
confidence: 99%
“…In an inflammatory context, they inhibit the proliferation of B lymphocytes and their production of immunoglobulins. Regarding innate immunity, they notably decrease the production of reactive oxygen species by neutrophils and promote the M2 anti‐inflammatory phenotype of macrophages 9 …”
Section: Mesenchymal Stem/stromal Cellsmentioning
confidence: 99%
“…Such insight led to first clinical trials, which found transfusion of MSCs contributed to accelerating hematopoietic recovery following high-dose myeloablative chemotherapy and reversing steroid-resistant graft versus host disease (GvHD) [ 26 ], and actual current clinical value of MSCs is primarily derived from immunomodulatory properties (demonstrated in Fig. 1 ), [ 11 , 27 , 28 ]. Since the first clinical trial using MSCs as cellular pharmaceutical agents, numerous clinical trials have been conducted to test the efficacy of MSC-based therapy and over 10,000 of patients have been administered with allogeneic or autologous MSCs for the treatment of various diseases [ 21 , 29 ] (Mesenchymal stem cells search at www.clinicaltrials.gov , accessed on 24 April 2020), including GvHD, myocardial infarction (MI), stroke, Crohn’s disease, multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), diabetes, lupus, arthritis, acute lung injury, Covid-19 [ 30 ], cirrhosis, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Cell therapy encompasses a broad clinical territory in which transplanted cells are used to terminate or reverse an assortment of disease processes, such as cardiovascular disease, [ 1,2 ] diabetes, [ 3 ] autoimmune disorders, [ 4 ] neurodegenerative disease, [ 5,6 ] and cancer. [ 7 ] The last decade has seen an exponential advancement of cell therapy technologies, with promising preclinical results finally yielding substantial clinical benefit using Chimeric Antigen Receptor T‐cell (CAR T) for treatment of hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%